Study of dynamic buckling of FG plate due to heat flux pulse - Czechowski, Leszek (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with a FEM analysis of dynamic buckling of functionally graded clamped plates under heat flux loading with huge power. The materials of structures as well as their properties are varying in each layer across the plate thickness formulated by the power law distribution. The heat flux was applied evenly to the whole ceramic surface. The analysis was developed in the ANSYS 14.5 software. The duration of the heat flux loading equal to a period of natural fundamental flexural vibrations of given structures was taken into consideration.
Keywords: dynamic buckling; heat flux; Finite Element Method (FEM); FGMs; ceramics